Compensation and reduction of carbon dioxide emissions in international aviation - Eryk Kłopotowski; Leszek Cwojdziński (Przegląd Komunikacyjny)
Abstract: Sustainable development, i.e. the coherence of economic and social progress with environmental protection, are goals that must be achieved in order to prevent global environmental degradation. Reducing the emission of harmful compounds and noise is a current problem raised in various sectors of the economy. Through the ICAO International Civil Aviation Organization, the aviation sector worldwide is committed to meeting its commitments to reduce air emissions from aircraft. Despite the dynamic development of the unmanned aerial vehicle sector, manned aviation remains the leading means of passenger and cargo transport in civil aviation. In view of the emission of compounds having a negative impact on the environment by airplanes, it was deemed necessary at the global level to take steps aimed at a real limitation of the functioning of aviation, which is destructive to the nature. The International Civil Aviation Organization (ICAO) has developed a program that introduces a new approach to reducing negative effects on the environment called CORSIA (Carbon Offsetting and Reduction Scheme for International Aviation). The article presents the principles of its operation and implementation, as well as the project phases. The practical impact of the CORSIA program on aircraft operators and examples of costs for operators related to the implementation of the project were indicated. The aspect of mutual coexistence for the CORSIA program and the EU CO2 emissions trading system (EU-ETS) was also raised. European Emissions Trading Scheme - also known as the "Community carbon market" or the ETS. It is the first, by 2017, the largest and currently the largest, after China, CO₂ emissions trading system in the world. Keywords: CORSIA, EU ETS, CO2; Emission; Civil aviation; Sustainable development of aviation